Spontaneous movements in the newborns: a tool of quantitative video analysis of preterm babies. (February 2021) - Tacchino, Chiara; Impagliazzo, Martina; Maggi, Erika; Bertamino, Marta; Blanchi, Isa; Campone, Francesca; Durand, Paola; Fato, Marco; Giannoni, Psiche; Iandolo, Riccardo; Izzo, Massimiliano; Morasso, Pietro; et al.
Highlights: The number of preterm babies is steadily growing world-wide and they have higher risk of neuro-motor-cognitive deficits, whose early detection is important to mitigate the severity of long-term disabilities. The observation of spontaneous movements in the first three months of age is known to identify infants at risk. The simple computerized video analysis system proposed in this study can provide a robust system of quantitative evaluation of spontaneous movements of infants in their natural environment (MIMAS). A preliminary evaluation in a realistic clinical setting suggests that this system can be well understood by the clinicians and is trusted because it was demonstrated that it is sensitive to the degree of maturation of the newborns and to the conditions at birth, i.e. preterm vs. full term babies at the 40 th gestational week. The novelty of the study it that the system, integrated with a well-structured Biobank, can make available to the clinical service focused on preterm babies a growing tool with diagnostic, prognostic and epidemiological purposes. Abstract: Background and Objectives: The number of preterm babies is steadily growing world-wide and these neonates are at risk of neuro-motor-cognitive deficits. The observation of spontaneous movements in the first three months of age is known to predict such risk. However, the analysis by specifically trained physiotherapists is not suited for the clinical routine, motivating the development of simple computerized video analysis systems, integrated with a well-structured Biobank to make available for preterm babies a growing service with diagnostic, prognostic and epidemiological purposes. Methods: MIMAS (Markerless Infant Movement Analysis System) is a simple, low-cost system of video analysis of spontaneous movements of newborns in their natural environment, based on a single standard RGB camera, without markers attached to the body. The original videos are transformed into binarized sequences highlighting the silhouette of the baby, in order to minimize the illumination effects and increase the robustness of the analysis; such sequences are then coded by a large set of parameters (39) related to the spatial and spectral changes of the silhouette. The parameter vectors of each baby were stored in the Biobank together with related clinical information. Results: The preliminary test of the system was carried out at the Gaslini Pediatric Hospital in Genoa, where 46 preterm (PT) and 21 full-term (FT) babies (as controls) were recorded at birth (T0) and 8-12 weeks thereafter (T1). A simple statistical analysis of the data showed that the coded parameters are sensitive to the degree of maturation of the newborns (comparing T0 with T1, for both PT and FT babies), and to the conditions at birth (PT vs. FT at T0), whereas this difference tends to vanish at T1. Moreover, the coding method seems also able to detect the few 'abnormal' preterm babies in the PT populations that were analyzed as specific case studies. Conclusions: Preliminary results motivate the adoption of this tool in clinical practice allowing for a systematic accumulation of cases in the Biobank, thus for improving the accuracy of data analysis performed by MIMAS and ultimately allowing the adoption of data mining techniques.